Austrian tricentric real-life analysis of molecular profiles of metastatic biliary tract cancer patients - Taghizadeh, Hossein; Schmalfuss, Theresa; Maj-Hes, Agnieszka; Singer, Josef; Prager, Gerald W. (Frontiers in Oncology, 2023)
Introduction Metastatic biliary tract cancer (BTC) is a rare and aggressive entity associated with poor prognosis. It represents a major challenge for adequate treatment strategies. In recent years, BTC has become a model for precision medicine in gastrointestinal oncology. Therefore, the analysis of the individual molecular profile in BTC patients may lead to targeted therapies for the benefit of patients. Methods In this Austrian, tricentric, real-world, retrospective analysis, we investigated patients diagnosed with metastatic BTC who underwent molecular profiling between 2013 and 2022. Results In total, 92 patients were identified in this tricentric analysis and 205 molecular aberrations, including 198 mutations affecting 89 different genes in 61 patients were found. The predominant mutations were in KRAS (n=17; 22.4%), TP53 (n=17; 22.4%), PIK3CA (n=7; 9.2%), FGFR2 (n=7; 9.2%), DNMT3A (n=7; 9.2%), IDH1 (n=7; 9.2%), IDH2 (n=6; 7.9%), CDKN2A (n=6; 7.9%), BAP1 (n=4; 5.3%), NF1 (n=4; 5.3%), and NF2 (n=4; 5.3%). Three patients had HER2 amplification. MSI-H status and FGFR2 fusion genes were each observed in two different patients. One patient had a BRAF V600E mutation. Eventually, 10 patients received targeted therapy, of whom one-half derived clinical benefit. Conclusions Molecular profiling of BTC patients is implementable in routine clinical practice and should be regularly employed to detect and exploit molecular vulnerabilities.